Divide and conquer: genetics, mechanism, and evolution of the ferrous iron transporter Feo in Helicobacter pylori - Gómez-Garzón, Camilo; Payne, Shelley M. (Frontiers in Microbiology, 2023)
Introduction Feo is the most widespread and conserved system for ferrous iron uptake in bacteria, and it is important for virulence in several gastrointestinal pathogens. However, its mechanism remains poorly understood. Hitherto, most studies regarding the Feo system were focused on Gammaproteobacterial models, which possess three feo genes (feoA, B, and C) clustered in an operon. We found that the human pathogen Helicobacter pylori possesses a unique arrangement of the feo genes, in which only feoA and feoB are present and encoded in distant loci. In this study, we examined the functional significance of this arrangement. Methods Requirement and regulation of the individual H. pylori feo genes were assessed through in vivo assays and gene expression profiling. The evolutionary history of feo was inferred via phylogenetic reconstruction, and AlphaFold was used for predicting the FeoA-FeoB interaction. Results and Discussion Both feoA and feoB are required for Feo function, and feoB is likely subjected to tight regulation in response to iron and nickel by Fur and NikR, respectively. Also, we established that feoA is encoded in an operon that emerged in the common ancestor of most, but not all, helicobacters, and this resulted in feoA transcription being controlled by two independent promoters. The H. pylori Feo system offers a new model to understand ferrous iron transport in bacterial pathogens.